Selective adsorption of biodegradable polymaleic acid for regulating the wettability difference at the fine coal–kaolinite interface - Wei Xiao; Yuping Fan; Xianshu Dong; Xiaomin Ma; Yuanpeng Fu; Yanze Mu; Maoqing Yang; Pengcheng Wen; Kangpei Jin; Dehao Li (Minerals Engineering, 2026)

Multiple magma sources and incremental assembly of the late Mesozoic Yunmengshan batholith, North China Craton: Constraints from zircon Hf-O isotopes and apatite geochemistry - Zi-Mu Li; Miao-Miao Ling-Hu; Shi Chen; Jin-Feng Sun; Ji-Heng Zhang; Ya-Dong Wu; Bao-Quan Zhou; Quan-Lin Hou; Jin-Hui Yang (Lithos, 2026)

Anion-potential-guided weak-solvation design for polycyanoacrylate gel polymer electrolytes in lithium metal batteries - Peiyang Dong; Zhongpeng Li; Wei Tang; Saihai Lei; Juan Wang; Yu Li; Weihao Zeng; Shichun Mu (Chemical Engineering Journal, 2026)

Triphasic sequential gas delivery via a photo-instructive hydrogel for enhanced diabetic skin wound healing - Jingwen Dong; Junjie Zhou; Shuguang Huang; Junmei Mu; Ye Tian; Zhifei Ding; Yihui Li; Aiping Wang; Zhanwei Zhou; Zeyu Xu; Minjie Sun (Chemical Engineering Journal, 2026)

Systematic review of naturally occurring benzylisoquinoline alkaloids (2015–2024): phytochemistry, bioactivity and structure-activity relationship - Jing Liu; Tao Liu; Mu-Yan Liu; Hui-Hui Li; Xiao-Yu Zhao; Hui Zhang; Yan Ge; Ze-Dong Nan (Phytochemistry, 2026)

Calvatia lilacina spores extract and engineered E. coli Nissle 1917 remodel the diabetic wound microenvironment through combined treatment - Tangtang He; Yan Li; Tiantian Dong; Tianjie Yuan; Wen Min; Ruoyu Mu; Jun Chen (Food Research International, 2026)

Enhancing composite emulsion stability through electrostatic modulation of polysaccharides-whey protein isolate interactions for probiotic encapsulation - Wei-Gang Xin; Yu-Hang Jiang; Yu-Han Dong; Yu-Hang Hou; Mu-Ying Du; Amel Ahmed Ibrahim; Zsolt Zalán; Hua-Yi Suo (Food Chemistry, 2026)

Seismic stability of anchored slopes: a comprehensive framework for coupled viscoelastic-rheological effects in anchoring cables and geomaterials - Fa-Qiao Qian; Ya-Hong Deng; Huan-Dong Mu; Fan Liu (Computers and Geotechnics, 2026)

Synthesis of Ni, Co, and Mn multi-metal oxide honeycomb materials for all-solid-state asymmetric supercapacitors - Yuanzhou Mu; Mengmeng Sun; Siyi Guo; Tingting Dong; Lizhong He (Chemical Engineering Journal, 2026)

Enhanced biomethane production associated with olivine-stimulated CO2 reduction in petroleum reservoir production water - Muhammad Javed; Muhammad Irfan; Le-Gang Chen; Bo Fang; Bo-Wen Wang; Ghulam Dastgir; Muhammad Kashif Javed; Lei Zhou; Yi-Fan Liu; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Bioresource Technology, 2026)

Study on the mechanism of selective flotation separation of fine coal and kaolinite enhanced by environmentally friendly small-molecule carboxylic acids - Wei Xiao; Yuping Fan; Xiaomin Ma; Jian Niu; Maoqing Yang; Xianshu Dong; Yuanpeng Fu; Zeyu Feng; Pengcheng Wen; Yanze Mu (Minerals Engineering, 2026)

Sustainable high internal phase emulsions based on millet bran nanocellulose and EGCG: Centrifugal fabrication, antioxidant reinforcement, and 3D printability - Mo Chen; Yu-hao Wu; Xu Guo; Jin-yue Sun; Nan Chen; Mu-xuan Wang; Qi-dong Ren; Mohamed A. Farag; Nilufar Z. Mamadalieva; Min Wang; Meng-qi Zhang; Chao Liu (Food Chemistry, 2026)

Effects of slab folding on magma production in the Sumatra subduction zone - Yongliang Bai; Jiahao Tian; Yuanpeng Liu; Dongdong Dong; Shiguo Wu; Sanzhong Li; Xuan Mu (Earth and Planetary Science Letters, 2026)

Investigation, Evaluation and Geoconservation of the Yardang Landforms in Dahaidao Region, Hami Basin, Xinjiang, NW China - Qing-Wei Song; Hong-Xu Mu; Zhao-Jie Chen; Xu-Dong Song; Xiu-Long Zhang; Ying Dong; Yi-En Xiao (Geoheritage, 2026)

Deciphering the mechanisms underlying regional heterogeneity of high-temperature Daqu through integrated electronic sensory, volatilome, and microbiome analysis - Yu Mu; Hong Zhang; Yingdong Pan; Ziyou Tian; Ying Huang; Liang Yang; Chunlin Zhang; Chi Zhao; Dong Li; Xudong Liu; Li Jiang (International Journal of Food Microbiology, 2026)

Water droplets in crude oil: A new window into microbiome and microbial activity in subsurface oil reservoirs - Qiao-Hui Wang; Yi-Fan Liu; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2026)

The Influence of Fibroblast Microenvironment on the Differentiation and Maturation of Stem Cell-Derived Cardiomyocytes - Yuliang Dong; Haozhe Jiang; Fan Zhou; Junsheng Mu (Stem Cell Reviews and Reports, 2026)

ROS regulate pollen germination and tube growth in Betula platyphylla with involvement of H2O2 and polyamine oxidase BpPAO2 - Chaoning Zhao; Wendi Mu; Jiaqi Shi; Jiayuan Shi; Bello Hassan Jakada; Gege Dou; Taihe Zhao; Huiyi Xie; Siyu Dong; Ying Wu; Xingguo Lan (Physiology and Molecular Biology of Plants, 2026)

A genetic clash of sister groups: first-ever intergeneric and interspecific mitogenome comparisons between two close gall midge genera (Cecidomyiidae: Cecidomyiinae: Cecidomyiini): the floral and veggie-versatile Contarinia and the mango-mad Procontarinia, with phylogenetic applications - Xiu-Fang Dong; Yi-Fan Zhang; Xu-Yuan Gao; Ning-Bo Ma; Yu Ji; Yan-Fei Li; Yi-Ran Mu; Zheng-Hao Yue; De-Wei Wei; Yong-Hao Yu; Hai-Li Qiao; Wen-Jun Bu; et al. (Arthropod-Plant Interactions, 2026)

Association of microplastic pollution with coral resilience in the presence of sea surface temperature anomalies - Xu Dong; Xiangang Hu; Kaishuo Lu; Kai Hu; Li Mu (Journal of Hazardous Materials, 2026)

Selenomethionine antagonizes sodium arsenite-induced reproductive toxicity in zebrafish - Yan Zhang; Huan Wang; Xinru Bo; Yangfan Xu; Lingtian Xie; Yunyang Li; Jingli Mu; Jialing He; Na Zheng; Baoquan Zhao; Hongxing Chen; Wu Dong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Iron oxide catalytic pyrolysis and iron oxide-steam catalytic gasification of epoxy resin: Mechanistic insights from experiments, ReaxFF MD and DFT - Meng Sun; Hongxin Liang; Zhen Wang; Jianbiao Chen; Yan Shang; Ming Dong; Liang Wang; Lin Mu (Chemical Engineering Journal, 2026)

A composite conductive hydrogel loaded with alginate/gelatin microspheres with micro-environmentally induced smart temporal regulation for acute myocardial infarction treatment - Lei Mu; Tongyang Li; Bowen Qiao; Ruonan Dong; Congcong Zhang; Xin He; Peixue Ling; Zheng Wang; Baolin Guo (Carbohydrate Polymers, 2026)

A simplified empirical ocean current profile model for offshore engineering from wind–wave inputs using Buckingham Π and depth-recursive reconstruction - Yun-Mu Jiang; Gang Li; Ding-Hao Yu; Zhi-Qian Dong (Ocean Engineering, 2026)

Unveiling the dynamic characteristics of Rosa roxburghii Tratt wine: A multi-omics and molecular docking study on commercial Saccharomyces cerevisiae and indigenous Hanseniaspora uvarum L31 during fermentation - Dong Li; Xiaoqin Zhang; Yu Mu; Lilan Chen; Huan Guo; Wenyue Yu; Guofang Xie; Hong Gao (Food Chemistry, 2026)

BiSSET-Net: Multi-factor Time Series Prediction of Pine Caterpillar Infestation Risk in Northeast China Based On Bidirectional LSTM and State Space Model - Jingzheng Zhao; Mingchang Wang; Xi Mu; Dong Cai; Fengyan Wang; Minshui Wang; Hongchao Fan (Journal of Geovisualization and Spatial Analysis, 2026)

Research perspectives and micropropagation of Cardioteucris cordifolia C. Y. Wu - Mu Ze; Binyue Zhang; Haoyu Ma; Zhun Sun; Ming Dong; Lijuan Zou (In Vitro Cellular & Developmental Biology - Plant, 2026)

Compressive sensing based seismic data acquisition a case study in northeast China - Jian-guo Chen; Guo-xu Shu; Sheng-qiang Mu; Yi-yuan Wang; Shou-dong Huo (Applied Geophysics, 2026)

Analysis of the morphological structure and metabolic characteristics of Moniezia in sheep - Qian Mu; Wan-Ling Yao; Bao-Shan Wang; Wen-Zhu Chai; Fu-Hua Liu; Zhen Huang; Yong-Cheng Meng; Jing Pan; Xi-Ping Fan; Wan-Hong He; Wang-Dong Zhang (Veterinary Parasitology, 2026)

Enhancement of ultra-high-pressure dewatering of fine coal slurry: Synergistic regulation mechanism of pore interface chemistry by polycarboxylate-CaO - Yuping Fan; Pengcheng Wen; Xiaomin Ma; Xianshu Dong; Ruxia Chen; Maoqing Yang; Wei Xiao; Yanze Mu (Fuel, 2026)

A smartphone-controlled microfluidic platform for rapid, sample-to-answer HLA-B*58:01 genotyping via LNA-enhanced duplex RPA - Xinpei Pang; Zhubing Lei; Xiang Mu; Shuang Wu; Wen-Fei Dong; Qian Mei (Chemical Engineering Journal, 2026)

GPP dominates the change of WUE trend in the future period - Haili Dong; Fei Tian; Peiwen Mu (Theoretical and Applied Climatology, 2026)

AI-driven discovery of natural product-derived FAK1 inhibitors for idiopathic pulmonary fibrosis - Xing-Yi Chen; Mei-Hong Lu; Bin Li; Ya Zhou; Li Liu; Hao Yang; Qiu-Yu Wang; Lin Chang; Yu-Lan Zhao; Dong-Mei Wang; Bin Li; Ben-Rong Mu (Molecular Diversity, 2026)

The Potential Drug Target (Glycolysis Pathway) of the Spore Stage of the Pathogen Enterocytozoon hepatopenaei in Shrimp Farming - Bo Zhu; Juan Feng; Dong Qian; Ping Zhuang; Changkao Mu; Jiong Chen; Rongrong Ma (Fishes, 2026)
Enterocytozoon hepatopenaei (EHP) is a specialized parasitic microsporidian that causes significant economic losses to the shrimp farming industry. The glycolysis pathway plays an important role in the survival of EHP spores in vitro. In this study, key enzyme genes involved in the glycolysis pathway of EHP were analyzed, and purified spores were treated with KOH and a low temperature (−20 °C) to promote or inhibit germination. Quantitative analysis and enzyme activity of the initiating key gene hexokinase (HK) and the core link gene glyceraldehyde 3-phosphate dehydrogenase (GAPDH) were conducted to explore the energy response characteristics of germinating spores. The results showed that HK and GAPDH genes had significant differences from the host, based on phylogenetic analysis. The expression of HK gene and enzyme activity increased after promoting germination treatment. The expression of the GAPDH gene was stable, but the activity of the GAPDH enzyme increased significantly after germination promotion. These findings indicate that the inhibition of the HK gene expression level and GAPDH protein level can block spore germination and invasion in vitro, which could be used as potential control targets for EHP.

Combined transcriptome and metabolome analyses reveal that galactose metabolism is vital for tobacco in response to low-nitrate stress - Dong Wang; Yongchang Wen; Haoran Xie; Mingxin Mu; Xianchao Peng; Junju Li; Jixian He; Xiaoli Liu; Yifei Lu; Bi Ren; Liming Lu; Liqin Li (Journal of Genetics, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Photoelectrotrophic denitrification and iron-sulfur-nitrogen cycle enhance nutrient removal in pyrite-amended constructed wetlands - Xiaoxiao Hou; Lingyun Mu; Yingying Liu; Yanping Xiao; Xinshan Song; Xiaoxiang Zhao; Dong An (Journal of Environmental Management, 2026)

Layered nitrogen application drives changes in nitrogen nutrition status of wheat by affecting key soil microbial clusters - Yang Zhou; Pengjia Wu; Yanjie Qu; Shengyan Pang; Haimeng Mu; Min Yang; Xiang Lin; Dong Wang (European Journal of Agronomy, 2026)

In situ natural-ester-grafted coating extends cellulose insulation paper service life: Hydrophobicity and thermal-aging resistance for high-voltage equipment - Wenrui Tian; Haoxiang Zhao; Haibao Mu; Huanmin Yao; Xiong Yang; Jiufeng Dong; Daning Zhang; Guanjun Zhang (Chemical Engineering Journal, 2026)

Adaptations in ancient oasis woodlands of the hyper-arid Tarim Basin, Northwestern China: charcoal and coprolite analyses - Kangkang Li; Konglan Shao; Ying Yang; Gill Plunkett; Robert Spengler; Bing Xu; Yong Wu; Xiaohong Tian; Dong Wei; Chunxue Wang; Huiqiu Shao; Guijin Mu; et al. (Archaeological and Anthropological Sciences, 2026)

Distinct and interactive effects of multiple consumers on plant trade‐offs and diversity in alpine meadows - Yimin Zhao; Peng Zhang; Junsheng Ke; Yilin Dang; Kui Hu; Zijian Yu; Hongying Jiang; Chenrui Wang; Wenjie Li; Jing Zhang; Dong Zhang; Xue Zhang; et al. (Ecology, 2026)
Plants face a fundamental trade‐off between acquiring resources for growth or interspecific competition and simultaneously investing in anti‐consumer defenses. These selective pressures shape species' life history strategies and promote stable coexistence. However, the specific roles of distinct consumer groups, particularly the often‐overlooked oomycetes, in driving growth–defense trade‐offs and sustaining plant diversity remain poorly understood. To this end, we conducted a factorial field experiment in an alpine meadow on the Qinghai‐Tibetan Plateau, manipulating the nitrogen supply (to test resource acquisition effects) and removing consumer groups (i.e., mammalian herbivores, fungi, and oomycetes) both individually and in combination. We used standardized major axis regression to investigate how plant species differentially allocate resources between growth, competition, and defense, and how such trade‐offs influence plant species diversity. Species' responses to nitrogen addition and consumer removal were positively correlated, supporting the existence of widespread growth–defense trade‐offs. The strength of this trade‐off varied significantly among consumer removal treatments, with fungi and herbivores exerting stronger effects than oomycetes. The removal of both herbivores and oomycetes amplified their individual impacts on plant growth–defense trade‐offs. Consistent with this pattern, the removal of fungi or herbivores, but not oomycetes, led to pronounced declines in plant diversity. Our findings reveal the divergent roles of individual consumer groups in shaping plant life history strategies and highlight that cross‐trophic interactions, particularly those involving herbivores or fungal pathogens, are critical for maintaining plant diversity.

Trace carbonyls in water reuse: Structure-dependent multi-barrier penetration and enhanced deep mineralization via dual-radical oxidation synergism - Yun-Peng Wu; Qian-Yuan Wu; Zi-Bo Jing; Yu-Ming Tian; Jiang-Lei Xiong; Mu-Da Han; Sheng-Mei Li; Er-Dong Wang; Wen-Long Wang (Water Research, 2026)

Finite-time adaptive event-triggered control for USV trajectory tracking combined with intrinsic curiosity sequential proximal policy optimization - Xiaoning Zhang; Yunsheng Fan; Shengli Dong; Zhipeng Shen; Dongdong Mu; Xiang Ye; Peng Liu (Ocean Engineering, 2026)

Chronological and climatic insights from Karst Cave Silt Sediment in Southwest China - Yuan-Yuan Mu; Qing-Duo Wang; Chang-Sheng Wang; Tian-Zhou Zhang; Shao-Qin Ma; Jing-Ming Yang; Hai-Cheng; Wen-Jun Sun; Jun-Yun Li; Yan-Min Dong; Lu-Peng Yu; Ting-Yong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Mining allergens in Cryptotympana atrata nymphs: integrating proteomics and homology-based bioinformatics - Yuan He; Shu-tao Sun; Jian-bo Xiao; Qi-dong Ren; Ying-ying Chen; Meng-qi Zhang; Mu-xuan Wang; Xu Guo; Jin-yue Sun; Chao Liu (Food Chemistry, 2026)

Highland barley arabinoxylans with distinct molecular features modulate retrogradation and in vitro digestibility of highland barley starch - Yonghui Dong; Tingting Mu; Xue Wu; Chunping Chen; Haiyu Wu; Lin Han; Caian He; Min Wang (Food Hydrocolloids, 2026)

Denitrification driven by varying concentrations of Mn (II) under no external carbon source conditions: Denitrification performance, nitrogen transformation and metabolic pathways - Lingyun Mu; Xiaoxiao Hou; Xinshan Song; Xiangzhou Meng; Dong An (Bioresource Technology, 2026)

A robust system for somatic embryogenesis and shoot organogenesis in Begonia grandis subsp. sinensis (A. DC.) Irmsch and genetic fidelity assessment of the regenerants - Feimin Ma; Zhengli Shan; Haonan Su; Ruijing Han; Wenjing Zhou; Mu Ze; Ming Dong; Qinggui Wu; Lijuan Zou (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Biomineralization and genome-based insights of Fe(III) reduction of the NaCl-tolerant Tessaracoccus oleiagri from an integral oilfield - Xinghao Liu; Jianbin Li; Fangyi Mu; Ding Dong; Dehao Lu; Jie Yang; Ting Xu; Shuyuan Deng; Fan Zhang; Yuehui She; Hao Dong (Journal of Environmental Chemical Engineering, 2026)

Sugarcane polyphenols modulate gut microbiota and odor-associated metabolites during in vitro fecal fermentation of elderly - Hongye Li; Yun Bian; Yi Wu; Xueqing Hang; Mengqing Zhang; Luchuan Gao; Yifei Dong; Tanhang Mu; Wei Zhao (Food Bioscience, 2026)

NeuProIO: A dual-action solid drug nanoparticle topical formulation for simultaneous intraocular pressure reduction and neuroprotection for glaucoma - Lei Xu; Mu Li; Lin Qi; Tzu-Chen Wang; Dong Liu; Vimalin Jeyalatha Mani; Hsin-Yin Chuang; Qingbo Yang; Ruipu Mu; Samira Mahdi; Da Huang; Honglan Shi; et al. (Chemical Engineering Journal, 2026)

A lightweight detection algorithm for cereal weed recognition based on deep learning - Xiao-Wei Dong; Lin-Feng Wang; Xi-Mu Zhang; Ming Wang; Wei-Kai Li (Crop Protection, 2026)

Beyond astaxanthin: The bioactive ingredients of Haematococcus pluvialis and their applications in food - Shu-tao Sun; Yan-jie Jiang; Jesus Simal-Gandara; Xu Guo; Shengxiang Yang; Ying-ying Chen; Meng-qi Zhang; Qi-dong Ren; Mu-xuan Wang; Jin-yue Sun; Ning-yang Li; Chao Liu (Trends in Food Science & Technology, 2026)

Dual mutations containing E198A in β-tubulin eliminate the negative cross-resistance between carbendazim and diethofencarb in Corynespora cassiicola - Jingkun Han; Jiamei Zhu; Jin Li; Dicheng Ma; Wei Mu; Hongqiang Dong; Feng Liu (Pesticide Biochemistry and Physiology, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Sensitivity analysis of design variables in semi-batch reverse osmosis for energy-efficient water treatment - Linyinxue Dong; Yumiao Song; Yuxuan Liu; Mo Xie; Dongyan Mu; Jungbin Kim (Journal of Cleaner Production, 2026)

Enrichment and cultivation of thermophilic Bathyarchaeia from oil reservoirs via systematic cultivation profiling - Qing-Ping He; Yi-Fan Liu; Bo-Wen Wang; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2026)

Revealing dissolution process and mechanism of montmorillonite by two stereoisomers of malic acids and its effect on the Cr(III) retention properties: Insights from DFT simulations and experimental studies - Jingjie Yang; Li Zeng; Yong Wang; Song Liu; Aiqin Wang; Liang Bian; Temirlan Arslanov; Bin Mu; Hailiang Dong; Peng Liu; Xiaobin Gu (Chemical Engineering Journal, 2026)

Bioconversion of CO2 to methane energy by Methanococcus maripaludis in newly-designed bioreactor system: Kinetic characteristics, parameter optimization and grid-quality production - Lei Zhou; Jie Gao; Le-Gang Chen; Yi-Fan Liu; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Bioresource Technology, 2026)

Signaling pathways and potential therapeutic agents in trastuzumab-induced cardiotoxicity - Haonan Zhang; Changxu Lu; Siyuan Cheng; Jingyi Wu; Anqi Hu; Zhongyi Mu; Dan Dong; Mingli Sun (Apoptosis, 2026)

Discovery of lignans and curcuminoids as the effective inhibitors of pancreatic lipase: structure-activity relationship and inhibitory mechanism - Jie Mu; Rui-Dong Wang; Yi-Shu Zhao; Tian-Chi Lu; Si-Si Chen; Yi-Jing Wang; Hua Wei; Li-Wei Zou (Natural Product Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Ni/Al-based additives for deep desulfurization of high-sulfur coal: Cooperative desulfurization and sulfur migration behavior - Zheng-Zhi Zhang; Zhan-Ku Li; Jing-Tao Yao; Mu-Xin Liu; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Cai Wang; Zhi-Ping Lei; Shi-Biao Ren; Heng-Fu Shui (Journal of Environmental Chemical Engineering, 2025)

Self-healing, highly stretchable, recyclable PU-curcumin elastomer with substrate-sensitive solid-state fluorescence - Linjie Wei; Xiubin Xu; Hongchun Mu; Wantong Lin; Jiahui Tang; Jieran Li; Jianwei Liu; Haitao Dong; Danfeng Yu; Xu Wu (Chemical Engineering Journal, 2025)

The critical role of mitophagy in cell senescence-mediated pulmonary fibrosis and potential therapeutic strategies - Xing-Yi Chen; Dong-Mei Wang; Ya Zhou; Li Liu; Tao Zhu; Zhao Ran; Mei-Hong Lu; Ben-Rong Mu (Molecular Biology Reports, 2025)

The landscape of decidual immune cells at the maternal–fetal interface in parturition and preterm birth - Mu Lv; Yuanhui Jia; Jiaqi Dong; Shengyu Wu; Hao Ying (Inflammation Research, 2025)

Multi-target surrounding control of spacecrafts with sensor faults: A quantitative prescribed performance approach with event-triggered mechanism - Jiyuan Yi; Zhongcheng Mu; Dong Ye; Sunhao Chu; Shufan Wu (Advances in Space Research, 2025)

Effects of phenological uniformity on prediction accuracy of wheat yield and biomass - Yandong Yang; Qing Li; Qinwen Lin; Huimin Wang; Yi Shi; Gengchen Wu; Yue Mu; Dong Jiang; Seishi Ninomiya (Field Crops Research, 2025)

Mapping urban ultrafine particle exposure in Guangzhou, China: Development of a high-resolution land-use regression framework for megacity - Qing-Guo Zeng; Qi-Zhen Wu; Bin Zhao; Mu-Wu Xu; Yun Zhu; Shi-Cheng Long; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Research, 2025)

Influence of heterogeneous mixed-wettability evolution on different phases CO2 displacement and storage efficiency mechanisms: Based on pore structure characterization - Peizhai Cheng; Pingchuan Dong; Bingtao Yang; Youheng Zhang; Dongyang Ma; Junchang Mu; Zhenshuo Wang (Advances in Water Resources, 2025)

Hourly photosynthetically active radiation prediction in solar greenhouses using Bayesian optimized machine learning and deep learning based on limited local weather data - Menglong Wu; Ruoyu Li; Chang Lv; Aihong Dong; Fei Mu; Wenquan Niu (Computers and Electronics in Agriculture, 2025)

Effects of β-hydroxy-β-methylbutyrate inclusion on growth performance and fillet quality of olive flounder Paralichthys olivaceus fed low fishmeal based diets - Chaoqing Wei; Zhenxia Su; Cancan Xia; Lu Li; Zhicheng Song; Hua Mu; Hanliang Cheng; Jianhe Xu; Zhiguo Dong; Binlun Yan; Lu Zhang (Aquaculture, 2025)

A pair of lignans isolated from Trachelospermum jasminoides and their anti-inflammatory activity - Chen-Yi Yan; Miao Wang; Yu-Ting Mu; Li-Lian Zhao; Yu-Liang Guo; Wei-Zhen Dong; Yun Deng; Da-Le Guo (Phytochemistry Letters, 2025)

Microencapsulation of Acer truncatum seed oil using chickpea protein isolate–low/high-methoxy citrus pectin complex coacervates: Preparation, stability analysis, and application in milk - Mo Chen; Bo Zhang; Min Wang; Jin-yue Sun; Mu-xuan Wang; Meng-qi Zhang; Ying-ying Chen; Qi-dong Ren; Shu-tao Sun; Mohamed A. Farag; Xu Guo; Chao Liu (Food Hydrocolloids, 2025)

Ubiquitination: A non-negligible modulator in doxorubicin-induced cardiotoxicity - Can Gao; Changxu Lu; Jinwen Wei; Zhongyi Mu; Mingli Sun; Dan Dong; Zhenning Liu (Chemico-Biological Interactions, 2025)

Exploring the potential mechanisms of Da ChaiHu decoction against pancreatic cancer based on network pharmacology prediction and molecular docking approach - Dong Mu; Beijin Chen; Xiaoli Liu; Shumei Zheng; Yong Zhang; Hua Ni; Dejiang Zhou (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

PRDM14 promoted NSCLC cell proliferation, migration and invasion via modulating H3K27me3-mediated PEBP1/Raf-1/MEK/ERK MAPK signaling - He Shi; Yunfei Jiang; Haijun Mu; Guohua Liu; Xinyue Cheng; Weili Kong; Xingqi Zhou; Xiaoqiang Wen; Xiao Wang; Yiyu Lin; Linyu Pan; Haiying Dong; et al. (Genes & Genomics, 2025)

The importance of fungal necromass in soil organic carbon: Insights from elevation gradients in arid regions - Mengfei Cong; Zhihao Zhang; Guangxing Zhao; Xinping Dong; Yan Lu; Lei Li; Yang Hu; Weiqi Wang; Zhaobin Mu; Akash Tariq; Jordi Sardans; Josep Peñuelas; et al. (Applied Soil Ecology, 2025)

What does the dairy farming bring to the desertified soil? A case study - Zixi Han; Jianfei Zeng; Xu Zhao; Yanyan Dong; Yongsong Mu; Sha Wei; Yong Hou; Ziyu Han (Agricultural Systems, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Polystyrene nanoplastics promote muscle cell senescence through microtubule hyper-stabilization-mediated mitophagy dysfunction and cGAS-Sting activation - Jie Cui; Xianlin Yue; Yajun Zhang; Bingjie Wang; Angela Mu; Shifeng Ren; Liwei Shao; Shanshan Zhu; Nan Zhang; Yu Lu; Hongjuan Cui; Dong Li; et al. (Journal of Hazardous Materials, 2025)

Enhancing methanogenesis from long-chain fatty acids (LCFA) and enrichment of novel bacteria with resuscitation-promoting factors - Bo Fang; Yi-Fan Liu; Hao-Xun Wei; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Bioresource Technology, 2025)

Impact of convergence rate and slab dip angle on island-arc magma generation - Yongliang Bai; Wenzhao Zhang; Shiguo Wu; Dongdong Dong; Xuan Mu; Jiahao Tian; Yuanpeng Liu (Journal of Oceanology and Limnology, 2025)

Liquid metal-transition metal oxide photoactive electrode with interfacial interlocking structure for photo-enhanced asymmetric micro-supercapacitor - Yue Liang; Jian Gao; Tong Shen; Nan Lu; Tian-Sheng Mu; Yong-Chao Zhang; Xiao-Dong Zhu (Chemical Engineering Journal, 2025)

Development of cell labeling and gene editing tools in urochordate Ciona - Xiang Li; Lu Mu; Hongzhe Peng; Sun Nyunt Wai; Longjun Pu; Bo Dong (Marine Life Science & Technology, 2025)
Urochordate Ciona spp. are ideal marine model organisms for studying embryogenesis and developmental and evolutionary biology. However, the effective implementation of genetic labeling and CRISPR/Cas9-based editing tools at cellular resolution remains challenging. This study successfully developed and validated a collection of Gateway-based vectors for cell labeling in Ciona spp. The destination vector sets contained two Gateway cassettes flanked by Minos sites, allowing the N- or C-terminal tagging of a protein of interest with various fluorescent markers. In addition, we optimized the CRISPR/Cas9 and CRISPR/dCas9 systems by incorporating P2A-mCherry, a fluorescent indicator for Cas9 expression at cellular resolution. We demonstrated the effective destruction or inhibition of target genes when CRISPR constructs were introduced into fertilized eggs. Furthermore, we engineered a dual fluorescence sensor system that helps visualize successful gene knockouts at the cellular level in specific tissues. The genetic tools developed in this study offer a robust method for gene expression, cell tracking, and subcellular protein localization while also facilitating tissue-specific functional analysis in Ciona embryos and other model systems.

Exploring lipid remodeling and antioxidant responses in Chlorella pyrenoidosa exposed to streptomycin sulfate stress - Linyinxue Dong; Liangliang Mu; Xuxiong Huang (Food Chemistry, 2025)

Construction of the dynamic measurement algorithm for well inclination and azimuth in strapdown stable platform - Feng Sun; Rui Zhang; Yi-feng Wang; Wei Chen; Hui-dong Mu; Rui-wen Feng (Applied Geophysics, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

A new control strategy of sulfate-reducing microorganisms and corrosion rate from a high-temperature oil reservoir by nitrate/nitrite coupling with nitrate-reducing bacteria - Lei Zhou; Jie Gao; Yu-Xuan Li; Jun Wu; Biao Wang; Yi-Fan Liu; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

Effect of on stereoisomers of lactic acids on microbially-mediated reductive dissolution of clay minerals: Insights from DFT and experimental studies - Jingjie Yang; Liang Bian; Aiqin Wang; Xiaofeng Zhao; Jianan Nie; Temirlan Arslanov; Bin Mu; Hailiang Dong; Mianxin Song; Li Zeng; Peng Liu; Xiaobin Gu (Applied Clay Science, 2025)

Deep learning-driven reconstruction of PM2.5 vertical profiles: A fusion of lidar and tower data - Zihuai Yi; Yan Xiang; Long Yun; Xi Mu; Zhenyi Chen; Yuanzhu Dong; Feilong Li; Yin Pan; Lihui Lv; Tianshu Zhang; Wenqing Liu (Journal of Cleaner Production, 2025)

Soil minerals regulate soil organic carbon accumulation through glomalin-related soil protein along an elevation gradient in a mountain arid ecosystem - Guangxing Zhao; Zhihao Zhang; Weiqi Wang; Mengfei Cong; Xinping Dong; Yanju Gao; Zhaobin Mu; Yan Lu; Lei Li; Akash Tariq; Jordi Sardans; Josep Penuelas; et al. (Environmental Research, 2025)

Parkinson's Disease and the Microbiota-Gut-Brain Axis: Metabolites, Mechanisms, and Innovative Therapeutic Strategies Targeting the Gut Microbiota - Zhao Ran; Ben-Rong Mu; Dong-Mei Wang; Xin-Huang; Quan-Hong Ma; Mei-Hong Lu (Molecular Neurobiology, 2025)

Lead/cadmium impacts on zeolite-tobermorite: Nutrient release and sediment stability - Yanfei Tian; Xianshu Dong; Chunsheng Deng; Dong Yang; Xiaoya Ma; Yanze Mu (Environmental Pollution, 2025)

Multiple-reprocessable guaiacol-derived epoxy vitrimer with disulfide crosslinks and closed-loop recycling of carbon fiber-reinforced composites - Kai Dong; Di Zhao; Yang Pang; Binghui Liu; Qian Liu; Tong Mu; Chengji Zhao (Chemical Engineering Journal, 2025)

An overview of the chirality of diet-related fatty acids, glycerolipids, and glycerophospholipids - Shu-tao Sun; Yan-jie Jiang; Xu Guo; Meng-qi Zhang; Qi-dong Ren; Jesus Simal-Gandara; Mu-xuan Wang; Xiao-jia Xue; Ning-yang Li; Chao Liu (Trends in Food Science & Technology, 2025)

Unveiling the metabolic heterogeneity and formation mechanism in Chinese typical Daqu based on Qu-omics - Yu Mu; Shangjie Yao; Ying Huang; Zhiyu Zhu; Dong Li; Ya Song; Zehuan Liu; Chunlin Zhang; Shirui Yu (Food Research International, 2025)

Maize kernel nutritional quality—an old challenge for modern breeders - Decui Li; Anqi Hao; Wen Shao; Weiwei Zhang; Fuchao Jiao; Haiyan Zhang; Xueyan Dong; Yuan Zhan; Xia Liu; Chunhua Mu; Zhaohua Ding; De Xue; et al. (Planta, 2025)

Microbiome changes and characteristics under nutrient injection for enhanced oil production at Daqing oilfield - Zi-Yue Fu; Wen-Tao Chen; Gui-Na Qi; Zhao-wei Hou; Yi-Fan Liu; Li-Bin Shou; Lei Zhou; Shi-Zhong Yang; Xiao-Lin Wu; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

Engineering molecular bridges for fabricating cross-linked LM-HPDMS highly sensitive capacitive sensors for wearable monitoring - Xiaoyao Zhou; Yongguang Yu; Lisong Dong; Qilong Zhou; Danyang Cao; Jiahua Zhu; Xiaohua Lu; Liwen Mu (Chemical Engineering Journal, 2025)

Single-atom nanozyme immunoassay with electron-rich property for clinical patient cancer detection - Qingshan Liu; Guo Li; Yang Cao; Yaoyao Ren; Qiong Qin; Lei Li; Hao Zhang; Qi Xin; Xiaoqun Gong; Lingyu Zhao; Shu Zhang; Yonghui Li; et al. (Chemical Engineering Journal, 2025)

Lycorine hydrochloride interferes with energy metabolism to inhibit chemoresistant glioblastoma multiforme cell growth through suppressing PDK3 - Qingsheng Dong; Wanxiang Niu; Maolin Mu; Chengkun Ye; Pengfei Wu; Shanshan Hu; Chaoshi Niu (Molecular and Cellular Biochemistry, 2025)

Enhancing immune defense against COVID-19: Alveolar delivery of mucosal vaccines - Pei-Huang Wu; Dong-Chun Hong; Chu Xie; Mu-Sheng Zeng; Cong Sun (Science Bulletin, 2024)

Phytocannabinoid-like meroterpenoids from twigs and leaves of Rhododendron spinuliferum - E-E Luo; Wu-Fen Yang; Zhao-Jie Wang; Ling-Yun Chen; Mu-Yuan Yu; Xiao-Dong Luo; Xu-Jie Qin (Phytochemistry, 2024)

Construction of Al-doped FeCoP nanosheet array with superhydrophilic/superaerophobic characteristics as a bifunctional electrocatalyst for activating alkaline overall water splitting - Jinmei He; Yuqing Wang; Leihuan Mu; Jiehui Li; Yurou Dong; Ying Zhang; Yuan Deng; Pu Feng; Mengnan Qu (Journal of Water Process Engineering, 2024)

Evaluating and enhancing the applicability of thermal comfort indices in diverse outdoor environments using Bayesian and random forest regression - Wenqiang Jing; Jiayan Liu; Zeming Qin; Teng Mu; Zhemin Ge; Yuting Dong (Energy and Buildings, 2024)

Polyol-assisted ternary deep eutectic solvent protective lignocellulose pretreatment for high-efficiency xylan utilization and ethanol production - Shan Li; Yang Wang; Qinghe Dong; Zitong Yuan; Tiancheng Mu; Zhimin Xue; Limin Cao (Carbohydrate Polymers, 2024)

Depth-dependent responses of soil bacterial communities to salinity in an arid region - Xinping Dong; Zhihao Zhang; Yan Lu; Li Li; Yi Du; Akash Tariq; Yanju Gao; Zhaobin Mu; Yuhe Zhu; Weiqi Wang; Jordi Sardans; Josep Peñuelas; et al. (Science of The Total Environment, 2024)

From flavor to function: A review of fermented fruit drinks, their microbial profiles and health benefits - Yu-Han Yuan; Dong-Dong Mu; Li Guo; Xue-Feng Wu; Xiang-Song Chen; Xing-Jiang Li (Food Research International, 2024)

Phenotypic characterization and genetic mapping of the semi-dwarf mutant sdw9 in maize - Jiawen Zhao; Baiyu Yuan; Hao Zhang; Xiao Guo; Liangfa Wang; Xiaoqian Qiu; QianKun Xie; Liqin Mu; Chenhui Ma; Teng Zhou; Javed Hussain; Xiaoyang Chen; et al. (Theoretical and Applied Genetics, 2024)

Coal-based graphene formation by CO2 laser scribing: Various structures and excellent electrochemical performance - Yungang Zhao; Shaoqing Wang; Xiaoling Wang; Lu Zhang; Jidun Sha; Xiaomei Zhang; Ruifeng Mu; Zeyu Dong (Fuel, 2024)

The role and mechanism of β-catenin-mediated skeletal muscle satellite cells in osteoporotic fractures by Jian-Pi-Bu-Shen formula - Yanghua Tang; Zhuosong Mu; Dong Pan; Renqi Liu; Shenghu Hong; Zhenfei Xiong (Journal of Molecular Histology, 2024)

Bi-allelic missense variants in MEI4 cause preimplantation embryonic arrest and female infertility - Zhiqi Pan; Weijie Wang; Ling Wu; Zhongyuan Yao; Wenjing Wang; Yao Chen; Hao Gu; Jie Dong; Jian Mu; Zhihua Zhang; Jing Fu; Qiaoli Li; et al. (Human Genetics, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

A culture-dependent analysis of anaerobic methylotrophs in oil reservoir systems - Lin-Yuan Huang; Yi-Fan Liu; Wan-Qi Qin; Shi-Yi Wang; Yuan-Hao Wang; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2024)

Revealing the comprehensive effect of mechanization on sauce-flavor Daqu through high-throughput sequencing and multi-dimensional metabolite profiling - Yu Mu; Ying Huang; Dong Li; Zhiyu Zhu; Shirui Yu; Feng Xie (Food Research International, 2024)

Methanogenic biodegradation of thermoplastic poly(vinyl alcohol) films produced by two manufacturing processes in enrichment cultures - Ming-Le Ji; Yi-Fan Liu; Yu Bai; Zhen Hu; James H. Wang; Jia-Yi Li; Wan-Qi Qin; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Yingcheng Li; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2024)

The effects and cell phenotype changes in Escherichia coli O157:H7 induced into VBNC state by l-malic acid at low temperature - Zequn Zhang; Yicong Shi; Tianlin Cui; Kangyi Mu; Fang Chen; Xiaojun Liao; Li Dong; Xiaosong Hu (Food Bioscience, 2024)

Investigation on the operating capacity expansion through parallel schemes of reciprocating-switcher energy recovery device for desalination: Simulation, verification and parameterization - Jie Zhou; Dong Liu; Qinghong Zhang; Chao Bian; Xiuxia Meng; Naitao Yang; Shichen Mu (Desalination, 2024)

Two new anti-inflammatory compounds from the roots and rhizomes of Clematis terniflora var . manshurica (Rupr.) Ohwi - Ping Shao; Sheng Dong; Lin-Tong Mu; Ling Han; Chong-Ning Lv; Jiu-Zhi Yuan; Jin-Cai Lu (Natural Product Research, 2024)

Environmental and human history in the hyper-arid eastern Tarim Basin (Lop Nur), northwest China: A critical review for sustaining the natural and cultural landscapes - Kangkang Li; Xiaoguang Qin; Bing Xu; Lei Zhang; Guijin Mu; Yong Wu; Xiaohong Tian; Dong Wei; Chunxue Wang; Huiqiu Shao; Hongjuan Jia; Zhiqiang Yin; et al. (Quaternary International, 2024)

Biocatalytic Au10 clusters for sepsis management via modulation of systemic inflammation - Qi Xin; Sufei Zhou; Lijie Zhang; Si Sun; Di Liu; Hao Wang; Xiaoyu Mu; Xiaoxing Fang; Qi Chen; Huanhuan Qiao; Xiao-Dong Zhang; Ruiping Zhang (Chemical Engineering Journal, 2024)

Impact of Climate Change on Water Diversion Risk of Inter‑Basin Water Diversion Project - Linhui Mu; Tao Bai; Dong Liu; Lei Li (Water Resources Management, 2024)

The positive effect of the enzyme inducer (MnSO4) on the formation of humic substance in rice straw composting by stimulating key microorganisms - Linying Mu; Runshi Dong; Jiaqi Wang; Jieyu Yue; Lina Pan; Caihong Song; Zimin Wei (Science of The Total Environment, 2024)

Long-term exposure to major constituents of fine particulate matter and neurodegenerative diseases: A population-based survey in the Pearl River Delta Region, China - Qi-Zhen Wu; Hui-Xian Zeng; John Andersson; Anna Oudin; Katja M. Kanninen; Mu-Wu Xu; Shuang-Jian Qin; Qing-Guo Zeng; Bin Zhao; Mei Zheng; Nanxiang Jin; Wei-Chun Chou; et al. (Journal of Hazardous Materials, 2024)

Landsat observations of total suspended solids concentrations in the Pearl River Estuary, China, over the past 36 years - Qiang Sun; Wei Luo; Xianzhang Dong; Shaohua Lei; Meng Mu; Shuai Zeng (Environmental Research, 2024)

Screening and identification of probiotics from the intestinal tract of largemouth bass (Micropterus salmoides) for use as a feed additive and bacterial infection control - Lu Xia; Gaofeng Cheng; Pan Wang; Xinyou Wang; Zhaoran Dong; Qingjiang Mu; Jiaqian Yu; Zhihao Jiang; Jun Xiao; Hao Feng; Xiangping Li; Weiguang Kong; et al. (Aquaculture, 2024)

Nitrate-dependent ferrous oxidation: Feasibility, mechanism, and application prospects for wastewater treatment - Lili Yang; Wenxuan Li; Jie Liu; Hongjuan Zhu; Hao Mu; Kaiyao Hu; Jie Li; Sanqiang Dong (Journal of Water Process Engineering, 2024)

Superior performance of hybrid model in ungauged basins for real-time hourly water level forecasting – A case study on the Lancang-Mekong mainstream - Zhiqiang Dong; Hongchang Hu; Hui Liu; Baoligao Baiyin; Xiangpeng Mu; Jie Wen; Dengfeng Liu; Lajiao Chen; Guanghui Ming; Xue Chen; Xiaochen Li (Journal of Hydrology, 2024)

Efficient trimethoprim removal via cooperation of radical and non-radical pathways in UV/peroxymonosulfate: Kinetics, mechanisms and disinfection by-products-associated risks - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Juan Wang; Yu-Qiong Gao; Dong-Su Bi; Bo Wang; Xing-Yan Mu; Xiao-Jun Hu (Journal of Environmental Chemical Engineering, 2024)

The key proteolytic enzyme analysis of industrial Aspergillus oryzae at solid-state koji fermentation with a local database extension - Yali Mu; Yueshu Li; Yumei Wu; Dong Wang; Lijie Zhang; Yan Xu (Food Bioscience, 2024)

Changes in sources and formation mechanisms of carbonaceous aerosols driven by short-term air pollution controls in Megacity Xi'an, China - Zimeng Zhang; Tong Sha; Zhen Mu; Jinwen Li; Zipeng Dong; Dyussenova Ainur; Jiale Ding; Xingxing Jiang; Tengfei Xu; Qingcai Chen (Atmospheric Environment, 2024)

Glyphosate exposure affected longevity-related pathways and reduced survival in asian honey bees (Apis cerana) - Dong Zhi-Xiang; Li Wan-Li; LI Xi-Jie; Li Jia-Li; Zhang Jun; Zhao Chong-Hui; Huang Qi; Cao Zhe; Chen Yuan; Zhao Hong-Mu; Guo Jun; Tian Wen-Li (Chemosphere, 2024)

Development and application of greenhouse light environment simulation technology based on light path tracing - Zhihui Mu; Yu Bo; Jihang Xu; Kai Song; Boda Dong; Jian Wang; Sheng Shu; Yu Wang; Shirong Guo (Computers and Electronics in Agriculture, 2024)

Development and evaluation of a haplotype reference panel of Zhikong scallop (Chlamys farreri) for genotype imputation - Mingyi Sui; Zhi Liu; Xiaowen Huang; Zujing Yang; Haitao Yu; Chang Cui; Yuqing Hu; Xuefeng Wang; Xiaojing Shen; Qianqian Mu; Mingxuan Teng; Ang Zhao; et al. (Aquaculture, 2024)

Microbial phylogenetic divergence between surface-water and sedimentary ecosystems drove the resistome profiles - Okugbe Ebiotubo Ohore; Jingli Zhang; Binessi Edouard Ifon; Mathieu Nsenga Kumwimba; Xiaoying Mu; Dai Kuang; Zhen Wang; Ji-Dong Gu; Guojing Yang (Science of The Total Environment, 2024)

Physiological and transcriptomic response reveals new insight into manganese tolerance of Celosia argentea Linn. - Liyun Liang; Mu Ze; Jun Yang; Qian Xu; Cunmei Du; Xiaohong Hu; Ming Dong; Lijuan Zou; Tuo Qi (Journal of Hazardous Materials, 2024)

Insights into major pigment accumulation and (non)enzymatic degradations and conjugations to characterized flavors during intelligent black tea processing - Yongcheng Zhang; Kangni Yan; Qunhua Peng; Shan Feng; Zhangfeng Zhao; Long Chen; Lin Ye; Jianyu Fu; Haipeng Lv; Dan Mu; Chunwang Dong; Zhi Lin; et al. (Food Chemistry, 2024)

“Green” electrostatic droplet-assisted forming cellulose microspheres with excellent structural controllability and stability for efficient Cr(VI) removal - Zhouyu Miao; Mengya Mu; Hou-Yong Yu; Yanjuan Dong (Carbohydrate Polymers, 2024)

Transformation of exogenous hexavalent chromium and imidacloprid in soils - Xian’an Yu; Tingting Mu; Tong Zhou; Yujuan Huang; Hong Chen; Changxun Dong; Longhua Wu; Peter Christie (Journal of Soils and Sediments, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

Biogeography and diversity patterns of functional genes associated with C, N, P, S cycling processes across China classical sea sediments - Shuai Liu; Xin Huang; Hongyu Mu; Minggang Zheng; Shaoping Kuang; Hui Chen; Yan Xu; Dong Wang; Huan Liu; Xuan Li (Science of The Total Environment, 2024)

Exploring the heterogeneity of community and function and correspondence of “species-enzymes” among three types of Daqu with different fermentation peak-temperature via high-throughput sequencing and metagenomics - Ying Huang; Dong Li; Yu Mu; Zhiyu Zhu; Yuzhang Wu; Qi Qi; Yingchun Mu; Wei Su (Food Research International, 2024)

Functions and mechanisms of sponge iron-mediated multiple metabolic processes in anaerobic ammonium oxidation - Lili Yang; Wenxuan Li; Hongjuan Zhu; Sanqiang Dong; Hao Mu; Kaiyao Hu; Te Wang; Jie Li (Bioresource Technology, 2023)

Modulating the coordination environment of Co single-atom catalysts through sulphur doping to efficiently enhance peroxymonosulfate activation for degradation of carbamazepine - Wei Zhang; Mu Li; Jingwen Luo; Guan Zhang; Lin Lin; Feiyun Sun; Mei Li; Zijun Dong; Xiao-yan Li (Chemical Engineering Journal, 2023)

Hierarchical extraction of cropland boundaries using Sentinel-2 time-series data in fragmented agricultural landscapes - Wenyao Song; Chen Wang; Taifeng Dong; Zhaohai Wang; Chengxin Wang; Xiaoda Mu; Huanxue Zhang (Computers and Electronics in Agriculture, 2023)

Biphasic high-entropy layered oxide as a stable and high-rate cathode for sodium-ion batteries - Jinxiao Mu; Tianxun Cai; Wujie Dong; Ce Zhou; Zhen Han; Fuqiang Huang (Chemical Engineering Journal, 2023)

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

Divergent structures of Mammalian and gammaherpesvirus uracil DNA glycosylases confer distinct DNA binding and substrate activity - Yunxiang Mu; Monika A. Zelazowska; Zaowen Chen; Joshua B. Plummer; Qiwen Dong; Laurie T. Krug; Kevin M. McBride (DNA Repair, 2023)

Machine learning improves prediction of severity and outcomes of acute pancreatitis: a prospective multi-center cohort study - Jia-Ning Li; Dong Mu; Shi-Cheng Zheng; Wei Tian; Zuo-Yan Wu; Jie Meng; Rui-Feng Wang; Tian-Lei Zheng; Yue-Lun Zhang; John Windsor; Guo-Tao Lu; Dong Wu (Science China Life Sciences, 2023)

Composition and transcriptional activity of oil reservoir microorganisms under different gas/liquid ratios - Li-Bin Shou; Zhao-Wei Hou; Yi-Fan Liu; Ying Wang; Lei Zhou; Jin-Feng Liu; Shi-Zhong Yang; Ji-Dong Gu; Xiao-Lin Wu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2023)

Insight into the structural feature, ash transformation behavior, and alkali metal heat release characteristic of industrial lignin via experimental and equilibrium evaluation - Hongchao Yin; Xiankun Huang; Lin Mu; Xi Xi; Ming Dong; Zhaoyi Huo (Fuel, 2023)

Mechanistic insights into dissolved organic matter-driven protistan and bacterial community dynamics influenced by vegetation restoration - Zhang-mu Jing; Qing-qian Li; Yan-jie Wei; Bin Dong; Peng Yuan; Rui-xia Liu; Hong-jie Gao (Environmental Research, 2023)

ADGB variants cause asthenozoospermia and male infertility - Ronggui Qu; Zhihua Zhang; Ling Wu; Qun Li; Jian Mu; Lin Zhao; Zheng Yan; Wenjing Wang; Yang Zeng; Ruyi Liu; Jie Dong; Qiaoli Li; et al. (Human Genetics, 2023)

Ecotoxicological risk assessment of 14 pesticides and corresponding metabolites to groundwater and soil organisms using China-PEARL model and RQ approach - Jiangong Jiang; Zhixin Liu; Beixing Li; Shankui Yuan; Ronghua Lin; Xin Yu; Xiao Liu; Xianxia Zhang; Ke Li; Dong Xiao; Shaoli Yu; Wei Mu (Environmental Geochemistry and Health, 2023)

Effects of solar radiation and fine roots on suction of Amorpha fruticose-vegetated soil - Han-qing Guo; Xiao-qing Chen; Dong-ri Song; Qing-yi Mu; Hamed Sadeghi; Hao Jiang; Ming Lv (Journal of Mountain Science, 2023)

The potential health risks of short-chain chlorinated paraffin: A mini-review from a toxicological perspective - Ying-Wen Mu; Dong Cheng; Cui-Li Zhang; Xiu-Lan Zhao; Tao Zeng (Science of The Total Environment, 2023)

Derivation and validation of soil cadmium thresholds for the safe farmland production of vegetables in high geological background area - Demiao Mu; Shunan Zheng; Dasong Lin; Yingming Xu; Ruyin Dong; Penggang Pei; Yuebing Sun (Science of The Total Environment, 2023)

Inducing itinerant ferromagnetism by manipulating van Hove singularity in epitaxial monolayer 1T-VSe2 - Junyu Zong; Zhao-Yang Dong; Junwei Huang; Kaili Wang; Qi-Wei Wang; Qinghao Meng; Qichao Tian; Xiaodong Qiu; Yuyang Mu; Li Wang; Wei Ren; Xuedong Xie; et al. (Science Bulletin, 2023)

5-epi-ent-Kaurane diterpenoids from the aerial parts of Isodon eriocalyx and their anti-atherosclerotic potential - Long Mu; Tian Li; Peng-Lin Wu; Ling-Qiao Cai; Shu-Ying Li; Zi-Yuan Wang; Yuan-Yuan Liu; Jie Wang; Dong Yan; Zheng-Yun Rao; Chao-Jun Wang; Jian Zhang; et al. (Phytochemistry, 2023)

Value-added utilization of hydroxy-substituted aromatics in coal-derived liquids - Zhi-Hao Ma; Sheng Li; Xue-Qian Dong; Cai-Xia Ju; Dan Mu; Zheng Yang; Min Li; Xian-Hou Guo; Zhi-Min Zong; Xing-Shun Cong; Xian-Yong Wei (Fuel, 2023)

Comparative investigation on the pyrolysis of crop, woody, and herbaceous biomass: Pyrolytic products, structural characteristics, and CO2 gasification - Lin Mu; Ranyu Wang; Pengwei Xie; Yonglin Li; Xiankun Huang; Hongchao Yin; Ming Dong (Fuel, 2023)

Comprehensive analysis for the bioturbation effect of space mutation and biofortification on strong-flavor Daqu by high-throughput sequencing, volatile analysis and metabolomics - Yu Mu; Jun Huang; Rongqing Zhou; Suyi Zhang; Hui Qin; Yi Dong; Chao Wang; Xiaojun Wang; Qianglin Pan; Huifang Tang (Food Chemistry, 2023)

Bifunctional electrocatalyst junction engineering: CoP nanoparticles in-situ anchored on Co3(Si2O5)2(OH)2 nanosheets for highly efficient water splitting - Yang Mu; Yifu Zhang; Ziyi Feng; Xueying Dong; Xuyang Jing; Xiaoyu Pei; Yunfeng Zhao; Zongkui Kou; Changgong Meng (Chemical Engineering Journal, 2023)

Bidirectional reflectance factor measurement of conifer needles with microscopic spectroscopy imaging - Yongkang Lai; Xihan Mu; Yuequn Bian; Xiaohan Dong; Feng Qiu; Xinyu Bo; Zhixiang Zhang; Yi Li; Xinli Liu; Linyuan Li; Donghui Xie; Guangjian Yan (Agricultural and Forest Meteorology, 2023)

Characteristics of microbiota, core sulfate-reducing taxa and corrosion rates in production water from five petroleum reservoirs in China - Lei Zhou; Jun Wu; Jia-Heng Ji; Jie Gao; Yi-Fan Liu; Biao Wang; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Science of The Total Environment, 2023)

Liquid metal @ mxene spring supports ionic gel with excellent mechanical properties for high-sensitivity wearable strain sensor - Lisong Dong; Xiaoyao Zhou; Shuxin Zheng; Zhongfan Luo; Yuxiang Nie; Xin Feng; Jiahua Zhu; Zhangzhong Wang; Xiaohua Lu; Liwen Mu (Chemical Engineering Journal, 2023)

Humic acid nature and compound structure together determine the capacity of soil to sorb Avermectin B1a and its derivatives - Tong-fang Jing; Da-xia Zhang; Yan Jin; Guo-dong Si; Bei-xing Li; Wei Mu; Feng Liu (Chemical Engineering Journal, 2023)

Structural characteristics and disruption ripple effect in a meso-level electric vehicle Lithium-ion battery supply chain network - Dong Mu; Huanyu Ren; Chao Wang; Xiongping Yue; Jianbang Du; Pezhman Ghadimi (Resources Policy, 2023)

High-efficient and recoverable Mo72V30@Fe3O4/C catalyst for oxidation of hydroxyfurfural - Mengdi Gong; Xin-Yu Wang; Mu-Qin Li; Wen-Xia Mu; Yun-Dong Cao; Hong Liu; Yu-Guang Lv; Xin-Hua Qi; Guang-Gang Gao (Fuel, 2023)

Effectiveness and degradation pathways of bisphenol A (BPA) initiated by hydroxyl radicals and sulfate radicals in water: Initial reaction sites based on DFT prediction - Qi Han; Mingming Wang; Feiyun Sun; Boping Yu; Zijun Dong; Pu Li; Jingwen Luo; Mu Li; Xingliang Jin; Zhiguang Dai (Environmental Research, 2023)

Structure engineering of Mn2SiO4/C architecture improving the potential window boosting aqueous Li-ion storage - Xueying Dong; Yang Mu; Liuxue Shen; Haowei Wang; Chi Huang; Changgong Meng; Yifu Zhang (Chemical Engineering Journal, 2023)

Comparisons of cirrus clouds and their linkages to meteorology at the SACOL and the SGP sites - Zixiang Dong; Jinming Ge; Ang Gao; Zeen Zhu; Jialin Yan; Qingyu Mu; Jing Su; Xuan Yang; Xiaoyu Hu (Atmospheric Research, 2023)

Protective Effects of Sepia Ink Melanin on Hepatic Tissue in Streptozotocin-Induced Diabetic Mice - Xiaopeng Wang; Meng Han; Hui Dong; Yun Zhao; Weiwei Song; Chunlin Wang; Changkao Mu; Ronghua Li (Journal of Ocean University of China, 2022)

Sestrin2 attenuates renal damage by regulating Hippo pathway in diabetic nephropathy - Yawei Bian; Chonglin Shi; Shan Song; Lin Mu; Ming Wu; Duojun Qiu; Jiajia Dong; Wei Zhang; Chen Yuan; Dongyun Wang; Zihui Zhou; Xuan Dong; et al. (Cell and Tissue Research, 2022)

Late Mesozoic rifting and its deep dynamic mechanisms in the central Sulu orogenic belt: Records from Lingshan Island - Tengfei Zhou; Yaoqi Zhou; Nina Søager; Paul Martin Holm; Zhenkai Zhang; Jun Wang; Zhao Liang; Hongyu Mu; Yanjun Cheng; Feifei Liu; Miao Wang; Yue Zhang; et al. (Science China Earth Sciences, 2022)

Risk Analysis of Dynamic Water Level Setting of Reservoir in Flood Season Based on Multi-index - Zhenyu Mu; Xueshan Ai; Jie Ding; Kui Huang; Senlin Chen; Jiajun Guo; Zuo Dong (Water Resources Management, 2022)

Discovery of the non‐cosmopolitan lineages in Candidatus Thermoprofundales - Yi‐Fan Liu; Liu Yang; Zhong‐Lin Liu; Jing Chen; Bo Fang; Lei Zhou; Jin‐Feng Liu; Shi‐Zhong Yang; Ji‐Dong Gu; Bo‐Zhong Mu (Environmental Microbiology, 2022)
Summary The recently proposed order Candidatus Thermoprofundales, currently containing only one family‐level lineage Marine Benthic Group‐D (MBG‐D), is distributed in global subsurface ecosystems and ecologically important, but its diversity, evolution and metabolism remain largely unknown. Here we described two novel family‐level specialized lineages in Ca . Thermoprofundales, JdFR‐43 and HyVt, which are restricted to specific biotopes (primarily in marine hydrothermal vents and occasionally in oil reservoirs and hot springs) in contrast to the cosmopolitan lineage MBG‐D. The comparative genomics revealed that the specialized lineages have streamlined genomes, higher GC contents, enriched genes associated with nucleotide biosynthesis, ribosome biogenesis and DNA repair and additional thermostable aminopeptidases, enabling them to adapt to high‐temperature habitats such as marine hydrothermal vents, deep subsurface oil reservoirs and hot springs. On the contrary, the unique metabolic traits of the cosmopolitan MBG‐D, motility, glycolysis, butanoate metabolism, secondary metabolites production and additional genes for specific peptides and carbohydrates degradation potentially enhance its response to environmental change. Substrate preference is found for most MAGs across all lineages with the ability to utilize both polysaccharides (chitin and starch) and proteinaceous substances, whereas JdFR‐43 members from oil reservoirs can only utilize proteins. These results expand the diversity of C a . Thermoprofundales significantly and further improve our understandings of the adaptations of C a . Thermoprofundales to various environments.

The IAMAS-CNC Early Career Scientists Nobel Prize Online Interpretation Workshop - Jing Li; Zhongjing Jiang; Yueming Dong; Lu Zhang; Tong Ying; Zhenyu Zhang; Mu Mu (Advances in Atmospheric Sciences, 2022)

Optimization of aquaculture sustainability through ecological intensification in China - Shuang‐lin Dong; Yun‐wei Dong; Ling Cao; Johan Verreth; Yngvar Olsen; Wen‐jing Liu; Qi‐zhi Fang; Yan‐gen Zhou; Li Li; Jing‐yu Li; Yong‐tong Mu; Patrick Sorgeloos (Reviews in Aquaculture, 2022)
As the world's leading producer of farmed aquatic food products, China faces great uncertainty concerning the further sustainable development of its aquaculture industry due to high and increasing pressure from environmental and resource constraints. To realize truly sustainable development, it is imperative to establish an evaluation system that integrates social, economic, environmental and resource criteria, and optimizes aquaculture systems through a holistic approach. Here, we used analytical hierarchy processes combined with expert judgment and objective data to assess the sustainability of 10 major aquaculture production systems (APSs) in China. Based on the evaluation results, we propose the ecological intensification of aquaculture systems (ELIAS), rationally integrating anthropogenic inputs with aquaculture ecosystem services, to improve the sustainability of APSs. The holistic evaluation system and ELIAS are fundamental and critical for the future development of aquaculture in China and globally.

Cover Image, Volume 14, Issue 3 - Shuang‐lin Dong; Yun‐wei Dong; Ling Cao; Johan Verreth; Yngvar Olsen; Wen‐jing Liu; Qi‐zhi Fang; Yan‐gen Zhou; Li Li; Jing‐yu Li; Yong‐tong Mu; Patrick Sorgeloos (Reviews in Aquaculture, 2022)
The cover image is based on the Review Article Optimization of aquaculture sustainability through ecological intensification in China by Shuang‐lin Dong et al., https://doi.org/10.1111/raq.12648 image

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

The synergistic effects of TGF-β1 and RUNX2 on enamel mineralization through regulating ODAPH expression during the maturation stage - Yuan Tian; Haiyu Mu; Zhiheng Dong; Yu Wang; Yuguang Gao; Yan Gao; Li Zhang (Journal of Molecular Histology, 2022)

Molecular characterization and expression analysis of hypoxia-inducible factor-1α, factor-2α, and factor-3α and physiological response to hypoxia exposure in Amur minnow (Phoxinus lagowskii) - Yuting Yang; Zhongdian Dong; Xi Chen; Zhen Wang; Dawei Zhang; Liqun Liang; Weijie Mu (Aquaculture International, 2022)

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Histopathological parameters, antioxidant enzyme levels, transcriptome, and hematology parameters of Amur minnow (Phoxinus lagowskii) infection with Tetrahymena pyriformis - Zhen Wang; Zhongdian Dong; Dawei Zhang; Liqun Liang; Weijie Mu (Aquaculture International, 2021)

Runx2 deficiency in junctional epithelium of mouse molars decreases the expressions of E-cadherin and junctional adhesion molecule 1 - Yuan Tian; Haiyu Mu; Aiqin Wang; Yan Gao; Zhiheng Dong; Yang Zhao; Cong Li; Li Zhang; Yuguang Gao (Journal of Molecular Histology, 2021)

Genome analysis of Salmonella phage vB_SalM_8-19 (genus Rosemountvirus) - Cong Cong; Wei Bing Dong; Cui Hui Jing; Yuan Yu Yu; Xu Yong Ping; Wang Li Li; Li Shu Ying; Li Ji Bin; Xu Mu; Li Xiao Yu (Archives of Microbiology, 2021)

Mechanical and Failure Characteristics of Rock-coal-rock Combined Body under Different Strain Rates: A Numerical Study from Micro Perspective - Shu-ning Dong; Ang Li; Ya-dong Ji; Yu-xuan Yang; Qian Mu (Geotechnical and Geological Engineering, 2021)

Effects of Al stress on the growth and nitrogen uptake of maize varieties with different Al tolerance as related with Al chemical forms on root surfaces - Xiao-ying Pan; Ge Dong; Xian He; Ru-hai Wang; Ren-kou Xu; Ting-ting Mu (Journal of Soils and Sediments, 2020)

Pure qP-wave least-squares reverse time migration in vertically transverse isotropic media and its application to field data - Jian-Ping Huang; Xin-Ru Mu; Zhen-Chun Li; Qing-Yang Li; Shuang-Qi Yuan; Yun-Dong Guo (Applied Geophysics, 2020)

Fine-mapping and transcriptome analysis of BoGL-3, a wax-less gene in cabbage (Brassica oleracea L. var. capitata) - Xin Dong; Jialei Ji; Limei Yang; Zhiyuan Fang; Mu Zhuang; Yangyong Zhang; Honghao Lv; Yong Wang; Peitian Sun; Jun Tang; Dongming Liu; Yumei Liu; et al. (Molecular Genetics and Genomics, 2019)

Comparative analysis of glucose metabolism responses of large yellow croaker Larimichthys crocea fed diet with fish oil and palm oil - Qi Wang; Hua Mu; Haohao Shen; Zhixiang Gu; Dong Liu; Mengxi Yang; Yue Zhang; Weiqi Xu; Wenbing Zhang; Kangsen Mai (Fish Physiology and Biochemistry, 2019)

Correction to: Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2019)

Effects of water content on the shear behavior and critical state of glacial till in Tianmo Gully of Tibet, China - Gordon G. D. Zhou; Lei-lei Chen; Qing-yi Mu; Kahlil Fredrick E. Cui; Dong-ri Song (Journal of Mountain Science, 2019)

Compression characteristics of saturated re-compacted glacial tills in Tianmo Gully of Tibet, China - Lei-lei Chen; Gordon G. D. Zhou; Qing-yi Mu; Kahlil Fredrick E. Cui; Dong-ri Song (Journal of Mountain Science, 2019)

Astaxanthin enhances hematology, antioxidant and immunological parameters, immune-related gene expression, and disease resistance against in Channa argus - Mu-Yang Li; Xin-Yu Liu; Chang-Ge Xia; Gui-Qin Wang; Dong-Ming Zhang (Aquaculture International, 2019)

Four new phenolic constituents from the rhizomes of Gastrodia elata Blume - Zhi-Wei Wang; Yun Li; Da-Hui Liu; Yan Mu; Hong-Jing Dong; Hong-Lei Zhou; Lan-Ping Guo; Xiao Wang (Natural Product Research, 2019)

Risk Assessment of Triclosan, a Cosmetic Preservative - Jung Dae Lee; Joo Young Lee; Seung Jun Kwack; Chan Young Shin; Hyun-Jun Jang; Hyang Yeon Kim; Min Kook Kim; Dong-Wan Seo; Byung-Mu Lee; Kyu-Bong Kim (Toxicological Research, 2019)

Genetic analysis of cob resistance to F. verticillioides: another step towards the protection of maize from ear rot - Cong Mu; Jingyang Gao; Zijian Zhou; Zhao Wang; Xiaodong Sun; Xuecai Zhang; Huafang Dong; Yanan Han; Xiaopeng Li; Yabin Wu; Yunxia Song; Peipei Ma; et al. (Theoretical and Applied Genetics, 2019)

Effects of dietary Allium mongolicum Regel polysaccharide on growth, lipopolysaccharide-induced antioxidant responses and immune responses in Channa argus - Mu-Yang Li; Xin-Ming Zhu; Xiao-Tian Niu; Xiu-Mei Chen; Jia-Xin Tian; Yi-Di Kong; Dong-Ming Zhang; Lei Zhao; Gui-Qin Wang (Molecular Biology Reports, 2019)

Novel mutations in ZP1, ZP2, and ZP3 cause female infertility due to abnormal zona pellucida formation - Zhou Zhou; Caixia Ni; Ling Wu; Biaobang Chen; Yao Xu; Zhihua Zhang; Jian Mu; Bin Li; Zheng Yan; Jing Fu; Wenjing Wang; Lin Zhao; et al. (Human Genetics, 2019)

Tilapia fisheries in Guangdong Province, China: Socio‐economic benefits, and threats on native ecosystems and economics - Dang En Gu; Fan Dong Yu; Ye Xin Yang; Meng Xu; Hui Wei; Du Luo; Xi Dong Mu; Yin Chang Hu (Fisheries Management and Ecology, 2019)
Tilapia is one of the groups of fish species most widely cultured globally. China has been the largest producer of tilapia in the world since 1990s. Guangdong Province produces almost 40% of all tilapia in China because of its suitable geography and weather conditions, and tilapia culture has brought considerable economic benefits. Unfortunately, many of the biological traits that make tilapia popular for culture also contribute to its success as an invader. Tilapia has invaded natural waters and has become the dominant fish in many rivers of Guangdong Province, causing economic loss in capture fisheries, and affecting native fish species, biodiversity and aquatic ecosystems. Poor fishery management, water quality degradation and biodiversity loss have all facilitated the tilapia invasion. Tilapia have filled the niches left vacant by now locally extinct native species resulting from environmental changes in freshwater ecosystems of the province. The introduction of tilapia has both advantages and disadvantages, which should be managed to use effectively the various tilapia species in aquaculture while controlling their spread in natural waters.

Human activity during the late Pleistocene in the Lop Nur region, northwest China: Evidence from a buried stone artifact - Kangkang Li; Xiaoguang Qin; Xiaoyan Yang; Bing Xu; Lei Zhang; Guijin Mu; Dong Wei; Chunxue Wang; Yong Wu; Xiaohong Tian; Yongchong Lin; Wen Li; et al. (Science China Earth Sciences, 2018)

Early Mesozoic magmatism and tectonic evolution of east-central Tibet - Yanfei Chen; Zeming Zhang; Zuolin Tian; Xin Dong; Huixia Ding; Hongchen Mu; Dongyan Kang; Yunshuai Li (International Journal of Earth Sciences, 2018)

High-Temperature Metamorphism, Anataxis and Tectonic Evolution of a Mafic Granulite from the Eastern Himalayan Orogen - Zeming Zhang; Huixia Ding; Xin Dong; Zuolin Tian; Dongyan Kang; Hongchen Mu; Shengkai Qin; Yuanyuan Jiang; Mengmei Li (Journal of Earth Science, 2018)

Identification and Field Evaluation of the Sex Pheromone of Orthaga achatina (Lepidoptera: Pyralidae) - Qi Yan; Hai-Dong Li; Yan Chen; Zhan-Feng Ye; Xi-Yu You; Jun Zhou; Lan-Fang Mu; Shi-Jing Liu; Xiang-Bo Kong; Sajjad Ali Khuhro; Shuang-Lin Dong (Journal of Chemical Ecology, 2018)

Hydrophilic modification and anti-fouling properties of PVDF membrane via in situ nano-particle blending - Wanying Xie; Ji Li; Tingting Sun; Wentao Shang; Wenyi Dong; Mu Li; Feiyun Sun (Environmental Science and Pollution Research, 2018)

An Evaluation of the Resilience of the Regional Agricultural Water and Soil Resource System in Heilongjiang Province, China - Dong Liu; Ran Mu; Qiang Fu; Chunlei Liu; Tianxiao Li; Khan M. Imran; Song Cui; Faiz M. Abrar (Agricultural Research, 2018)

Long non-coding RNA (lncRNA) MAGI2-AS3 inhibits breast cancer cell growth by targeting the Fas/FasL signalling pathway - Yong Yang; Hong Yang; Miao Xu; Haibin Zhang; Mingtao Sun; Peng Mu; Tongbao Dong; Shanmei Du; Kui Liu (Human Cell, 2018)

Anaerobic biodegradation of partially hydrolyzed polyacrylamide in long-term methanogenic enrichment cultures from production water of oil reservoirs - Hao Hu; Jin-Feng Liu; Cai-Yun Li; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Biodegradation, 2018)

Roles of flotillins in tumors - Xu-xu Liu; Wei-dong Liu; Lei Wang; Bin Zhu; Xiao Shi; Zi-xuan Peng; He-cheng Zhu; Xing-dong Liu; Mei-zuo Zhong; Dan Xie; Mu-sheng Zeng; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2018)

Characterization of bacterial composition and diversity in a long-term petroleum contaminated soil and isolation of high-efficiency alkane-degrading strains using an improved medium - Jun Zheng; Jun-Qiao Feng; Lei Zhou; Serge Maurice Mbadinga; Ji-Dong Gu; Bo-Zhong Mu (World Journal of Microbiology and Biotechnology, 2018)

Propionate metabolism and diversity of relevant functional genes by in silico analysis and detection in subsurface petroleum reservoirs - Tao Yang; Serge Maurice Mbadinga; Lei Zhou; Shi-Zhong Yang; Jing-Feng Liu; Ji-Dong Gu; Bo-Zhong Mu (World Journal of Microbiology and Biotechnology, 2017)

Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2017)
Cystatin SN (CST1) belongs to the type 2 cystatin (CST) superfamily, which restricts the proteolytic activities of cysteine proteases. CST1 has been recently considered to be involved in the development of several human cancers. However, the prognostic significance and function of CST1 in breast cancer remains unknown. In the current study, we found that CST1 was generally upregulated in breast cancer at both mRNA and protein level. Furthermore, overall survival (OS) and disease-free survival (DFS) in the low CST1 expression subgroup were significantly superior to the high CST1 expression subgroup (OS, p < 0.001; DFS, p < 0.001), which indicated that CST1 expression level was closely correlated to the survival risk of these patients. Univariate and multivariate analyses demonstrated that CST1 expression was an independent prognostic factor, the same as ER status and nodal status. Next, CST1 overexpression promoted breast cancer cell proliferation, clonogenicity, migration, and invasion abilities. By contrast, knockdown of CST1 attenuated these malignant characteristics in breast cancer cells. Collectively, our study indicates that CST1 cannot only serve as a significant prognostic indicator but also as a potential therapeutic target for breast cancer. Key messages High CST1 expression is negatively correlated with survival of breast cancer patients. CST1 promotes cell proliferation, clone formation, and metastasis in breast cancer cells. CST1 is a novel potential prognostic biomarker and therapeutic target for breast cancer.

Puerarin-7-O-glucuronide, a water-soluble puerarin metabolite, prevents angiotensin II-induced cardiomyocyte hypertrophy by reducing oxidative stress - Ning Hou; Bin Cai; Cai-Wen Ou; Zhen-Hui Zhang; Xia-Wen Liu; Mu Yuan; Gan-Jian Zhao; Shi-Ming Liu; Long-Gen Xiong; Jian-Dong Luo; Cheng-Feng Luo; Min-Sheng Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Expression of SoxC Transcription Factors during Zebrafish Retinal and Optic Nerve Regeneration - Zhaoxia Mu; Shuqiang Zhang; Chunjiao He; Haitao Hou; Dong Liu; Nan Hu; Hui Xu (Neuroscience Bulletin, 2017)

NOX2 Mediated-Parvalbumin Interneuron Loss Might Contribute to Anxiety-Like and Enhanced Fear Learning Behavior in a Rat Model of Post-Traumatic Stress Disorder - Fang-fang Liu; Lin-dong Yang; Xiao-ru Sun; Hui Zhang; Wei Pan; Xing-ming Wang; Jian-jun Yang; Mu-huo Ji; Hong-mei Yuan (Molecular Neurobiology, 2016)

Methylenebisnicotiflorin: a rare methylene-bridged bisflavonoid glycoside from ripe Pu-er tea - Mu-Ke Tao; Min Xu; Han Zhang; Hui Chen; Chang Liu; Hong-Tao Zhu; Dong Wang; Chong-Ren Yang; Ying-Jun Zhang (Natural Product Research, 2016)

One new cycloartane triterpene glycoside from Beesia calthaefolia - Jin-Yuan Zhao; Li-Hua Mu; Xian-zhe Dong; Yuan Hu; Ping Liu (Natural Product Research, 2016)

IL-1α-induced microvascular endothelial cells promote neutrophil killing by increasing MMP-9 concentration and lysozyme activity - Xiaoye Liu; Hong Dong; Mingming Wang; Ying Gao; Tao Zhang; Ge Hu; Huiqing Duan; Xiang Mu (Immunologic Research, 2016)

Molecular characterization of Beclin 1 in rare minnow (Gobiocypris rarus) and its expression after waterborne cadmium exposure - Xiao-Hong Liu; Zhi-Jian Wang; Dong-Ming Chen; Mu-Fei Chen; Xing-Xing Jin; Jing Huang; Yao-Guang Zhang (Fish Physiology and Biochemistry, 2016)

A novel MVK missense mutation in one Chinese family with disseminated superficial actinic porokeratosis - Wen-sheng Lu; Xiao-dong Zheng; Xiu-hua Yao; Lan-fang Zhang; Mu-Qiu Wang; Fa-Xing Jiang; Si-Ping Zhang; Bai Hu (Molecular Biology Reports, 2014)

Prognostic significance of TBX2 expression in non-small cell lung cancer - Bo Hu; Hai-Ping Mu; Yu-Qing Zhang; Chong-Yi Su; Jian-Tao Song; Chong Meng; Dong-Xing Liu (Journal of Molecular Histology, 2014)

New cycloartane triterpene glycosides from Beesia calthaefolia - Hong-Jie Li; Li-Hua Mu; Xian-Zhe Dong; Xiao-Yue Ge; Ping Liu (Natural Product Research, 2013)

Erratum to: UDP-glucuronosyltransferase 1A1 is the principal enzyme responsible for puerarin metabolism in human liver microsomes - Cheng-Feng Luo; Bin Cai; Ning Hou; Mu Yuan; Shi-Ming Liu; Hong Ji; Long-Gen Xiong; Wei Xiong; Jian-Dong Luo; Min-Sheng Chen (Archives of Toxicology, 2012)

UDP-glucuronosyltransferase 1A1 is the principal enzyme responsible for puerarin metabolism in human liver microsomes - Cheng-Feng Luo; Bin Cai; Ning Hou; Mu Yuan; Shi-Ming Liu; Hong Ji; Long-Gen Xiong; Wei Xiong; Jian-Dong Luo; Min-Sheng Chen (Archives of Toxicology, 2012)

Analyses of n-alkanes degrading community dynamics of a high-temperature methanogenic consortium enriched from production water of a petroleum reservoir by a combination of molecular techniques - Lei Zhou; Kai-Ping Li; Serge Maurice Mbadinga; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Ecotoxicology, 2012)

Optimisation of preparation conditions and properties of phytosterol liposome-encapsulating nattokinase - Xu-Yan Dong; Fan-Pi Kong; Gang-You Yuan; Fang Wei; Mu-Lan Jiang; Guang-Ming Li; Zhan Wang; Yuan-Di Zhao; Hong Chen (Natural Product Research, 2012)

Positive allelopathic stimulation and underlying molecular mechanism of achyranthe under continuous monoculture - Zhen-Fang Li; Zi-Guan Zhang; Dong-Feng Xie; Lin-Quan Dai; Lan-Fang Zhu; Ji Li; Zong-Quan Liu; Yan-Qiu Yang; Lin-Kun Wu; Mu-Ji Huang; Zhong-Yi Zhang; Wen-Xiong Lin (Acta Physiologiae Plantarum, 2011)

Development and characterization of a mouse floxed Bmp2 osteoblast cell line that retains osteoblast genotype and phenotype - Li-an Wu; Junsheng Feng; Lynn Wang; Yan-dong Mu; Andrew Baker; Kevin J. Donly; Stephen E. Harris; Mary MacDougall; Shuo Chen (Cell and Tissue Research, 2011)

Effect of high glucose concentration on VEGF and PEDF expression in cultured retinal Müller cells - Hua Mu; Xiao-Mei Zhang; Jian-Ju Liu; Li Dong; Zhuo-Lei Feng (Molecular Biology Reports, 2009)

Polymorphisms within promoter of Japanese flounder (Paralichthys olivaceus) ovary cytochrome P450-c19 (CYP19a) gene associated with reproductive traits - Feng He; Hai Shen Wen; Shuang Lin Dong; Bao Shi; Cai Fang Chen; Lian Shun Wang; Jun Yao; Xing Jiang Mu; Yu Guo Zhou (Fish Physiology and Biochemistry, 2009)

Hypertonic saline resuscitation maintains a more balanced profile of T-lymphocyte subpopulations in a rat model of hemorrhagic shock - Yuan-qiang Lu; Xiu-jun Cai; Lin-hui Gu; Han-zhou Mu; Wei-dong Huang (Journal of Zhejiang University-SCIENCE B, 2007)

Production of transgenic creeping bentgrass Agrostis stolonifera var. palustris plants by Agrobacterium tumefaciens-mediated transformation using hygromycin selection - Ning Han; Dong Chen; Hong-Wu Bian; Min-Juan Deng; Mu-Yuan Zhu (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)